Is platelet-lymphocyte ratio (PLR) a predictor of thrombosis and together with circulating tumor cells capable to determine recurrence-free survival in patients with gastric cancer? - Bruno Soriano Pignataro; Emne Ali Abdallah; Celso Abdon Lopes Mello; Vinicius Fernando Calsavara; Kenji Nishinari; Anna Paula Carreta Ruano; Marcello F. Fanelli; Guilherme Yazbek; Ludmilla Thomé Domingos Chinen (Brazilian Journal of Oncology)
Introduction: Cancer-associated thrombosis (CAT) is a major cause of morbidity and mortality in oncology patients. There are no accurate risk assessment tools to predict venous thromboembolism (VTE). Circulating tumor cells (CTCs), circulating tumor microemboli (CTM), and high platelet-lymphocyte ratio (PLR) may predispose to VTE. Objective: To evaluate correlations of CTCs, CTM, and PLR with VTE and recurrence-free survival (RFS) in gastric cancer patients. Material and Methods: Patients with gastric cancer (localized and metastatic disease) were recruited (March 2016 to April 2017). CTCs were analysed by ISET at two timepoints: before neoadjuvant treatment (CTC1) and after surgery/before adjuvant therapy (CTC2) for patients with localized disease, and before first-line chemotherapy (CTC1) and after 6 months (CTC2) for patients with metastases. VTE incidence was determined retrospectively. RFS was estimated by Kaplan-Meier analysis. Results: We evaluated 93 patients. According to Khorana scores, 63 (67.7%) patients were at intermediate and 30 (32.3%) were at high risk for VTE. VTE incidence was 20.4% and CTM were found in 39.8%. VTE developed in 7/37 (18.9%) CTM-positive and in 11/50 (22%) CTM-negative patients (p=0.93). When PLR >288, VTE occurred in 7/14 patients (p=0.005). PLR also associated with poor RFS (p<0.0001). CTC2 was associated with poor RFS (p<0.0001). CTC2, PLR and VTE were independent prognostic factors for RFS (p=0.005, 0.043, and <0.0001, respectively). Conclusion: PLR is a prognostic indicator for VTE and RFS in gastric cancer patients. Neither CTC, nor CTM improved risk stratification for VTE in our studied population. PLR, CTC2, and VTE were independent prognostic factors for RFS.